Pengaruh Kompleksitas Perusahaan, Leverage, & Kompensasi Terhadap Fee Audit Pada Perusahaan BUMN 2017-2021 - Muhammad Aria Gymnastiar; Annisa Nurbaiti (Owner : Riset dan Jurnal Akuntansi, 2023)
Audit Fees are a reward the auditor receives from the client entity in connection with providing audit services. Public accountants are very important in balancing information asymmetry and conflict of interest. Payment of this audit fee is based on a contract between the company and a public accounting firm based on an engagement letter. With this audit fee, the auditor must fulfill his duties and responsibilities. The research problem formulation is whether there is a simultaneous and partial effect of company complexity, leverage, and compensation on audit fees. The primary objective of this study was to examine the impact of company complexity, leverage, and compensation on audit fees within state-owned companies that are listed on the Indonesia Stock Exchange during the period spanning from 2017 to 2021. The present study employs a quantitative research methodology. The population under investigation in this study comprises state-owned companies that were listed on the Indonesia Stock Exchange during the period of 2017-2021. A total of 13 companies were selected as research samples. The employed methodology utilizes panel data regression as the primary analytical technique. The employed data analysis techniques encompass the descriptive statistical test, classic assumption test, panel data regression model testing, and hypothesis testing. The findings of this study suggest that there is a simultaneous impact of company complexity, leverage, and compensation on audit fees. The presence of partial functions is associated with a detrimental impact of company complexity on audit fees. The utilization of leverage and the provision of compensation positively impact the determination of audit fees. It is anticipated that future researchers will possess the capacity to broaden the scope of their research objectives and incorporate additional variables beyond those initially considered. It is anticipated that corporations will furnish comprehensive information regarding the audit fee